Підтримання публічного обвинувачення в суді – конституційна функція органів прокуратури України - Назарук, О.; Nazaruk, O. (Східноєвропейський національний університет імені Лесі Українки, 2016)
В статті розглянуто особливості реформування функціональної спроможності органів прокуратури на даному етапі розвитку правових відносин в державі. Визначено місце функції підтримання публічного обвинувачення в суді в системі функцій прокуратури. Запропоновано розглядати функцію підтримання публічного обвинувачення в суді не лише в інституційно- правовому, але й процесуальному аспектах. Окреслено напрями реформування чинного законодавства в досліджуваній сфері.The article describes the peculiar features and trends of reforming the functional responsibilities of the prosecution at modern stage of legal relationships development in Ukraine. The emphasis is laid on the role of the realization of public prosecution function in the court as an integral part of the prosecutor's office functions system. The author claims that content of the maintenance of public prosecution function should be formed within the framework of the criminal proceedings, where its practical implementation is realized, and therefore other regulations that define this activity of the prosecutor should be brought into complete accordance with the Constitution of Ukraine. It is stressed that the public prosecutor, as one of the central figures in the criminal proceedings, should be obliged to ensure compliance with the objectives of criminal justice when performing his duties. It has been suggested to consider the function of maintaining public prosecution in the court not only at the institutional and legal levels, but also in the procedural aspects. The article analyses the directions of reforming the existing legislation in this part with regard to the systemic principle.
Maintaining Public Prosecution in Court - the Constitutional Function of the Prosecution Authorities in Ukraine.
Keywords: функції прокуратури; прокурор; кримінальне провадження; обвинувачення; державне обвинувачення; публічне обвинувачення; суд; Prosecutor's functions; a prosecutor; criminal proceedings; prosecution; he state prosecution; public prosecution; court